Young consumers’ brand distrust model: Understanding the antecedents of young consumers’ distrust of brands - Tuominen, Jesse; Sormanen, Niina; Hietajärvi, Lauri; Luoma-aho, Vilma; Wilska, Terhi-Anna (Elsevier BV, 2025)
Consumer research has shown that brands benefit from consumers' trust in them. However, although consumers' distrust of brands can accordingly have harmful effects on brands, the antecedents of young consumers' brand distrust are not entirely clear. This study proposes a model for young consumer's brand distrust antecedents based on the integration of our findings and prior research. Manual coding and latent Dirichlet allocation were utilized to analyze online research panel participants' open-ended responses on what makes them distrust brands on social media. Our examination revealed several antecedents of young consumers' brand distrust in the context of social media, such as reputation issues, advertising issues, impression management, and commercial collaboration. This study significantly contributes to consumer research by addressing the understudied topic of what makes young consumers distrust brands within the social media context.